Proceedings of 2019 Chinese Intelligent Systems Conference Volume I - Jia, Yingmin; Du, Junping; Zhang, Weicun (Lecture Notes in Electrical Engineering, 2020)
XI, 771 p. 417 illus., 226 illus. in color.